Development of Diorama Media as an Innovation in Water Cycle Learning in Science Subjects Assisted by Worldwall (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
This study aims to develop diorama media as a learning aid for the water cycle in Natural Science (IPA) among fifth-grade students at Tanah Kalikedinding I/251 Elementary School, Surabaya. The research employed a Research and Development (R&D) method, adapting the 4D development model (Define, Design, Develop, and Disseminate). The diorama media underwent expert validation involving two material experts and two media experts, who assessed the product using specific criteria related to content accuracy, visual clarity, and user engagement. The average validation score reached 91% (very valid), confirming the feasibility of the developed media. Field testing was conducted on 35 students from one school, which limits the external validity and generalizability of the findings. Pretest results showed an average score of 62 (sufficient), while posttest results increased to 84 (good), with an N-Gain value of 0.58 (moderate-effective). Student responses were also highly positive, with 95% agreeing that the diorama made learning easier and more engaging. Implementation observations revealed that 92% of learning activities proceeded as planned. The diorama’s effectiveness aligns with Piaget’s cognitive development theory, Bruner and Vygotsky’s constructivism, and Mayer’s multimedia learning theory, emphasizing the importance of concrete experiences, visualization, and social interaction. Therefore, despite its limited sample scope, this diorama media demonstrates potential as an innovative and effective tool for improving elementary students’ conceptual understanding of the water cycle.